Three-dimensional stretching/shrinking flow of hybrid nanofluid with slips and Joule heating - Wahid, Nur Syahirah; Md Arifin, Norihan; Khashi’ie, Najiyah Safwa; Pop, Ioan; Bachok, Norfifah; Hafidzuddin, Mohd Ezad Hafidz (AIAA International, 2022)
Hybrid nanofluid has emerged as a remarkable heat transfer fluid due to its promising thermal characteristics. Despite that, a continuous investigation should still be conducted to overcome certain challenges in actual applications and provide a solution in controlling fluid behavior. Therefore, in this study, the authors intend to model and analyze the three-dimensional magnetohydrodynamic radiative hybrid nanofluid flow over a permeable stretching/shrinking surface with slips and joule heating. The similarity transformation is adapted to convert the leading equations into ordinary differential equations. The resulting equations are then evaluated with the facilitation of the BVP4C solver in MATLAB. The skin-friction coefficient and the local Nusselt number are presented in the form of graph for the selected pertinent effects. The solutions are found to be nonunique. Therefore, stability analysis is conducted, and the flow is only stable for the first solution. The presence of high copper volumetric concentration and velocity slip condition has delayed the boundary-layer separation process, which occurred at the shrinking surface region. A lower amount of volumetric concentration of copper is sufficient to enhance the heat transfer rate.